Redescription of Ecdyonurus (Ecdyonurus) russevi Braasch & Soldán, 1985 (Ephemeroptera: Heptageniidae) - Godunko, Roman J.; Vidinova, Yanka; Soldán, Tomáš (Zootaxa, 2015)
This study is focussed on the redescription of Ecdyonurus (Ecdyonurus) russevi Braasch & Soldán on the basis of the type material (holotype and paratypes) and topotypes collected in the Strandzha Mts. (Bulgaria). Female imago and subimago, larva and egg of the species are described for the first time and the male imago is redescribed in detail. The features distinguishing the species from other representatives of the genus Ecdyonurus are presented. Ecdyonurus russevi differs by the combination of several characters in the colour pattern of abdominal terga and wings, colour of lateral portion of male eyes and male genitalia structure in adults; some overlap has been observed in the number of groups of setae, bristles and hair-like setae on maxillae and labial palps, shape of pronotal projection and colour of tarsi in larvae; and insignificant number of knob-terminated coiled threads on exochorion, with only a few such attachment elements on one pole in eggs. Biology and present distribution of the species are discussed.